Reprodutibilidade do teste de Atividade de Vida Di??ria AVD-Glittre em indiv??duos hemipar??ticos decorrente de Acidente Vascular Encef??lico (AVE) - Teod??sio, Amanda da Concei????o (2016)
The stroke can cause several sequels compromising the neuromuscular, cardiorespiratory system and consequently the performance of the functional activities. For this, an evaluation tool is needed that incorporates the capacity and the functional performance of these individuals. The ADL Glittre test proposes this objective, being already validated in individuals with COPD, but not yet applied in the population with neurological alterations. Objective: To analyze the reproducibility of the ADL Glittre test in hemiparetic individuals due to stroke. METHODS: Patient profiles were plotted for gender, age, anthropometric data, side and site of injury, motor impairment (Fugl Meyer), Mental State (Mini Mental) and Functional Mobility Scale (FMS). The ADL Glittre test was performed with the upper limb not affected, its main outcome being the completion time. For reproducibility, the subject was submitted to four evaluative moments, two intra-rater evaluations and two inter-rater evaluations, adopted randomly. Variables were normalized by the Shapiro-Wilk test, reliability by means of the Intra-Class Correlation Coefficient (ICC), the Intra and Interim Concordance by means of Standard Error of Measure (EPM) and Minimum Changeable Detection (MMD). Results: There was a significant difference in the intra-rater evaluations (1 and 2), but the differences were smaller than the MMD (1.27 and 1.14 seconds). There was no significance in the outcome of the test in the inter-rater evaluations (p = 0.20). Conclusion: The Glittre AVD is reproducible for the hemiparetic population, which I completed in approximately five minutes. Due to the learning effect it is necessary to apply the test and retest.